1876 Tex. Gen. Laws 29, An Act To Incorporate The City Of Galveston And to Grant A New Charter, Tit. 7, Art. II, § 108 - (:unkn) unknown (My University, 1876)
To direct, control and prohibit the keeping and management of houses, or any building for the storing of gun-powder and other combustible, explosive or dangerous materials, within the city; to regulate the keeping and conveying of the same, and the use of candles and other lights in stables and other like houses.
Keywords: GUNPOWDER - STORAGE